New Modeling and Simulation Platform for Communications Systems:(I) Double Sideband Suppressed Carrier AM Modulator DSB-SC - Ahmed, H. A. (Engineering, Technology & Applied Science Research, 2012)
The main goal of this paper is to introduce a new platform for the implementation and simulation of communication systems. SCILAB/SCICOS is an open source software for conducting communication system related experiments, aiming to provide an experimentation platform for research on communication theories. Double Sideband Suppressed Carrier (DSB-SC) Modulator is modeled and simulated using this platform.